2021
DOI: 10.1039/d1cc01312b
|View full text |Cite
|
Sign up to set email alerts
|

Plug-and-play aqueous electrochemical atom transfer radical polymerization

Abstract: A simplified ‘plug-and-play’ approach to aqueous electrochemical atom transfer radical polymerization has been developed. Well-controlled polymerization of PEGA480 (Ɖm = 1.17 – 1.31) is reported under potentiostatic (3-electrodes, undivided cell)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…This indicated that the conditions currently employed are not suitable for obtaining a similar range of dispersities (Đ = 1.1 -1.6). For methacrylates, electrochemical ATRP may offer a solution to obtain lower Đ 43,[47][48][49] but this was deemed to be beyond the scope of the current work. To further probe the potential of our methodology, we were also interested in the limits of livingness for high-Đ systems as high Đ has traditionally been associated with chain termination.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the conditions currently employed are not suitable for obtaining a similar range of dispersities (Đ = 1.1 -1.6). For methacrylates, electrochemical ATRP may offer a solution to obtain lower Đ 43,[47][48][49] but this was deemed to be beyond the scope of the current work. To further probe the potential of our methodology, we were also interested in the limits of livingness for high-Đ systems as high Đ has traditionally been associated with chain termination.…”
Section: Resultsmentioning
confidence: 99%
“…Galvanostatic eATRP should be the preferred choice for large volume reactions due to the simpler and less expensive setup, and it has previously been successfully used. [31][32][33][34] To test galvanostatic electrolysis on a Cu cathode, a series of experiments was performed (Table 3) under continuous galvanostatic electrolysis (CGE). Initially, CGEs were attempted with a Cu/Cu pair and a single I app value (Table 3, entries 1-4).…”
Section: Entrymentioning
confidence: 99%
“…In the 10 years since this discovery, eATRP has been employed for the synthesis of polymers with a variety of compositions and architectures including block copolymers, bioconjugates, star and gra (co)polymers. [14][15][16][17][18][19][20][21][22] It is compatible with aqueous 23,24 and organic 10 media whilst heterogeneous systems such mini-emulsion [25][26][27][28] and surface-initiated (si-eATRP) [29][30][31][32] polymerizations have also been reported. Furthermore, the complex reaction set-up, initially involving a 3-electrode divided electrochemical cell, has been simplied by the use of sacricial counter electrodes (typically Al-wire), enabling undivided cells to be used in either 3-electrode (potential controlled) or 2-electrode (current controlled) congurations giving rise to simplied electrochemical atom transfer radical polymerisaiton (seATRP).…”
Section: Introductionmentioning
confidence: 99%
“…33 This development is signicant as it enables the chemistry to be performed using commercial, standardized hardware. 24 The most widely studied systems for aqueous eATRP employ Cu II X salts with tetradentate ligands tris(2-(dimethylamino) ethyl)amine (Me 6 -Tren) 10,34,35 or tris(2-pyridylmethyl)amine (TPMA). 33,36,37 They form more active complexes, having high K ATRP values.…”
Section: Introductionmentioning
confidence: 99%